Quality assessment of ambusang suman enriched with malunggay (Moringa oliefera) powder - Toriano, Sarah Jean Protacio (2010.)
Ambueong suman is a popular indigenos snack food in Aklan, consumed by children and adults.
Sotech thesis.
Keywords: Ambueong suman; Malunggay--Moringa oliefera